2017
DOI: 10.1016/j.cpr.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive meta-analysis of interpretation biases in depression

Abstract: Interpretation biases have long been theorized to play a central role in depression. Yet, the strength of the empirical evidence for this bias remains a topic of debate. This meta-analysis aimed to estimate the overall effect size and to identify moderators relevant to theory and methodology. PsycINFO, Embase, Web of Science, Scopus, PubMed, and dissertation databases were searched. A random-effects meta-analysis was performed on 87 studies (N=9443). Results revealed a medium overall effect size (g=0.72, 95%-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
200
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(248 citation statements)
references
References 104 publications
22
200
1
Order By: Relevance
“…These findings align with previous research suggesting that Western cultures have a strong desire to minimize negative self‐related information and personal control and responsibility for negative events, when compared to East Asians who instead tend to have greater tolerance of negative self‐information and responsibility for negative experiences (Bjorck et al ., ; Fry & Grover, ; Kitayama et al ., ). Despite these cultural differences, we found that, regardless of cultural group, those with depression reported significantly greater negative, control, and responsibility appraisals than controls, which is consistent with the negative interpretation biases observed during depression (Everaert, Podina, & Koster, ). Furthermore, these memory appraisals differentiated between Asian participants with and without depression in a similar pattern to that observed in the European Australian group.…”
Section: Discussionsupporting
confidence: 83%
“…These findings align with previous research suggesting that Western cultures have a strong desire to minimize negative self‐related information and personal control and responsibility for negative events, when compared to East Asians who instead tend to have greater tolerance of negative self‐information and responsibility for negative experiences (Bjorck et al ., ; Fry & Grover, ; Kitayama et al ., ). Despite these cultural differences, we found that, regardless of cultural group, those with depression reported significantly greater negative, control, and responsibility appraisals than controls, which is consistent with the negative interpretation biases observed during depression (Everaert, Podina, & Koster, ). Furthermore, these memory appraisals differentiated between Asian participants with and without depression in a similar pattern to that observed in the European Australian group.…”
Section: Discussionsupporting
confidence: 83%
“…Whelton and Greenberg () were among the first who studied self‐critical processes marked by self‐contempt in dysthymic individuals. They showed that the cognitive contents of the self‐criticism were similar across participants, consistent with what was found in the meta‐analysis by Everaert et al (). However, when the researchers tried to predict incremental symptom loads in their sample, the nonverbal and paraverbal emotional processes of self‐contempt were the only factor differentiating individuals with more or less depressed mood.…”
Section: Contempt As a Transdiagnostic Variablesupporting
confidence: 84%
“…the self-criticism were similar across participants, consistent with what was found in the meta-analysis by Everaert et al (2017). However, when the researchers tried to predict incremental symptom loads in their sample, the nonverbal and paraverbal emotional processes of self-contempt were the only factor differentiating individuals with more or less depressed mood.…”
supporting
confidence: 76%
“…Similarly, these participants may have engaged in more stimulusindependent cognition and/or idiosyncratic interpretation during less emotional (and perhaps less engaging) moments, which could account for the inverse association between functional typicality and symptom severity observed across the clip. Although speculative, this candidate explanation aligns with interpretation bias, a phenomenon in which depressed individuals adopt rigid, overly pessimistic responses to emotional (and especially negatively valenced) information (3,46,54,55). This set of findings deserves close consideration in future studies, as interpretation bias represents just one possible explanation for these observed effects.…”
Section: Discussionmentioning
confidence: 56%